2009
DOI: 10.1002/tcr.20173
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing interlocked molecules dynamically

Abstract: As the complexity of mechanically interlocked molecular architectures increases, it is important to understand the underlying principles, such as molecular recognition and self-assembly processes, that govern the practice of template-directed synthesis necessary to create these particular compounds. In this review, we explain the importance of dynamic processes in the synthesis of mechanically interlocked compounds. We show how many different dynamic covalent bonds have been used in the synthesis of rotaxanes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 221 publications
0
19
0
1
Order By: Relevance
“…One of the most common strategies in applying DCC for interlocked molecules is the so-called "clipping" method, 20 (Figure 2a). 21 The desired [2]rotaxane 4 was obtained quantitatively in a few minutes.…”
Section: By Imine Chemistrymentioning
confidence: 99%
“…One of the most common strategies in applying DCC for interlocked molecules is the so-called "clipping" method, 20 (Figure 2a). 21 The desired [2]rotaxane 4 was obtained quantitatively in a few minutes.…”
Section: By Imine Chemistrymentioning
confidence: 99%
“…Die frühen Synthesen von Catenanen, Rotaxanen und Knoten über Metallionentemplate wurden von Sauvage und Mitarbeitern zusammengefasst, [1] wobei der neueste Schwerpunkt auf der Verwendung solcher Strukturen als Prototypen für molekulare Maschinen liegt. [2] Außerdem wurden weitere Arten von statistischen Methoden [3] und Templatverfahren [4] (p-p-Wechselwirkungen, [5] Wasserstoffbrücken, [6][7][8] Ionenpaarbildungen, [9] hydrophobe Wechselwirkungen, [10] Anionen, [11] Radikale [12] und dynamische Anordnungen [13] ) zu mechanisch verbundenen Molekülen zusammengefasst. Hier konzentrieren wir uns auf die metallionengesteuerte Anordnung von verschlungenen Molekülen im Hinblick auf Synthesestrategien und -taktiken, einem "trickreichen" Zugang, der die Verwendung von Metallionen als Template, als Katalysatoren zur Bildung mechanischer Verbindungen und als wesentliche Strukturelemente umfasst.…”
Section: Anordnen Von Bausteinen Um Ein Metallionentemplatunclassified
“…[11,13,14] The energetic bias towards interlocked architectures renders dynamic covalent chemistry-the chemistry of thermodynamically controlled bond formation-a powerful tool in the creation of mechanical bonds. [15] Numerous reversible covalent bond forming reactions, including imine, acetal, hydrazone, and ester formation as well as Aldol, Diels-Alder, Michael, nucleophilic substitution, and olefin metathesis reactions, have been used to prepare mechanically interlocked compounds in high yields; [12,14,[16][17][18][19][20] however, the work described herein exploits disulfide exchange in the dynamic covalent assembly of catenanes and rotaxanes. Research undertaken by Sanders et al have demonstrated the success of such an approach by synthesizing a range of electron-rich 1,5-dialkoxynaphthalene and electron-deficient 1,4,5,8-naphthalene tetracarboxylic diimide catenanes [16,18,21,22] and even a trefoil knot [7] via disulfide exchange from simple building blocks.…”
Section: Introductionmentioning
confidence: 97%
“…For example, in a clipping protocol for [2]rotaxane synthesis, the free macrocycle can form in addition to the desired rotaxane, thus reducing the yield of interlocked products. [11,12] If, however, reversible or dynamic bonds are used in the macrocycle formation, any non-interlocked macrocycle produced can reopen and reassemble around the dumbbell, thereby introducing a "proof-reading" mechanism. [13] As mechanically interlocked molecules are typically lower in free energy than their non-interlocked counterparts, increased yields of interlocked architectures are often observed.…”
Section: Introductionmentioning
confidence: 99%